Fabrication of Quartz Crystal Microbalance Coated with GO/PVC Nanofiber for Benzene Detection as Tuberculosis Biomarker - Nugroho, Doni Bowo; Kamal, Nada Nadzira Ayasha; Wati, Rosita; Resfita, Nova (National Research and Innovation Agency, 2025)
Tuberculosis (TB) is a highly contagious illness and a major contributor to global mortality, with over 1.5 million deaths reported annually. TB is caused by Mycobacterium tuberculosis (Mtb), which is often difficult to diagnose in the early stages of infection. Existing diagnostic methods are limited by long processing times, high costs, and suboptimal sensitivity. Therefore, this study aimed to develop a Quartz Crystal Microbalance (QCM)-based biosensor employing polyvinyl chloride (PVC) nanofibers coated with graphene oxide (GO) for rapid detection of volatile TB biomarkers, particularly benzene. The sensing platform utilized a 10 MHz AT-cut silver electrode QCM coated with electrospun PVC nanofibers, followed by GO deposition via immersion. Scanning Electron Microscopy (SEM) showed uniform nanofibers with diameters increasing from 183 ± 54 nm to 348 ± 50 nm after GO coating, while FTIR confirmed the presence of GO functional groups. Sensor evaluation revealed a clear and concentration-dependent frequency shift, with a sensitivity of 1.88 Hz·L/mg, a strong linear correlation (R² = 0.99) across 1.18–23.68 mg/L, and a fast response time of 71 seconds. The limits of detection and quantification were determined to be 0.88 mg/L and 2.66 mg/L, respectively. Adsorption followed the Langmuir isotherm model, indicating monolayer uptake. These results demonstrate that the GO/PVC nanofiber-coated QCM offers a promising, low-cost, and sensitive approach for TB biomarker detection in breath analysis.